PchR, a regulator of ferripyochelin receptor gene (fptA) expression in Pseudomonas aeruginosa, functions both as an activator and as a repressor. - Heinrichs, D E (1996)
The product of the pchR gene, an AraC-like regulatory protein, is required for production of the FptA ferric pyochelin receptor in response to iron limitation and pyochelin (D. E. Heinrichs and K. Poole, J. Bacteriol. 175:5882-5889, 1993). The influence of iron, pyochelin, PchR, and FptA on fptA and pchR gene expression was assessed with fptA-lacZ and pchR-lacZ transcriptional fusions. As was expected, the expression of fptA decreased dramatically following the inactivation of pchR by the insertion of an OmegaHg cartridge, although the effect (> 10-fold) was not as dramatic as that of pyochelin deficiency, which obviated fptA gene expression. Insertional inactivation of pchR in a pyochelin-deficient (Pch-) background restored fptA expression to levels observed in the pyochelin-producing (Pch+) PchR- strain, suggesting that PchR represses fptA expression in the absence of pyochelin. Consistent with this, the cloned gene caused a five-fold decrease in the expression of the fptA-lacZ fusion in Escherichia coli. pchR gene expression was inducible by iron limitation, a result in agreement with the previous identification of a Fur box upstream of the gene, although the magnitude of the induction was less than that observed for fptA in response to iron limitation. Expression of pchR was effectively absent in a pyochelin-deficient strain, and insertional inactivation of pchR in a Pch+ or Pch- background caused an increase in pchR gene expression. PchR, thus, negatively regulates its own expression. Two related heptameric sequences, CGAGGAA and CGTGGAT, were identified upstream of the putative -35 region of both fptA and pchR and may function as a binding site for PchR. Insertional inactivation of fptA caused a marked decrease in fptA expression in a Pch+ background and obviated the apparent repression of fptA expression in a Pch- background, reminiscent of the effect of a pchR mutation. The fptA mutant did not, however, exhibit a defect in pchR expression. Interestingly, fptA mutants were unable to grow in the presence of pyochelin, suggesting that FptA is the sole outer membrane receptor for ferric pyochelin. These data indicate that PchR functions as both an activator and a repressor in controlling the expression of fptA and pchR. The involvement of FptA in this control is unclear, although it may be important in mediating the pyochelin effect on fptA expression, possibly by modulating PchR activity.